Rantakadun taloja etualalla, taustalla kylpylä ja kirkko - J. Reinberg
fyysinen kuvaus: vaaka
Keywords: puurakennukset; asuinrakennukset; katteet; kadut; kirkkorakennukset; ilmakuvat; pihat; parvekkeet; tuulimyllyt; mäet; kalliot; purjeveneet; aidat; liikerakennukset; kylpylät; varastorakennukset; aitat; katot; katot; Suomi, Naantali, Naantali